The fate of diclofenac in anaerobic fermentation of waste activated sludge. (15th November 2022) - Yang, Jingnan; Duan, Abing; Wang, Jianwu; Yang, Xianli; Liu, Xuran; Xiao, Fengjiao; Qin, Fanzhi; Yu, Yali; Wang, Dongbo
Abstract: Diclofenac (DCF), a nonsteroidal anti-inflammatory drug, is one of the most commonly detected pharmaceuticals in wastewater treatment plants. However, the fate of DCF in waste activated sludge (WAS) anaerobic fermentation has not been well-understood so far. This work therefore aims to comprehensively reveal whether and how DCF is transformed in WAS mesophilic anaerobic fermentation through both experimental investigation and density functional theory (DFT) calculation. Experimental results showed that ∼28.8% and 45.8% of DCF were respectively degraded during the batch and long-term fermentation processes. Based on the detected intermediates and DFT-predicted active sites, three metabolic pathways, i.e., chlorination, hydroxylation, and dichlorination, responsible for DCF transformation were proposed. DFT calculation also showed that the Gibbs free energy (ΔG) of the three transformation pathways was respectively 19.0, −4.3, and −19.3 kcal/mol, suggesting that the latter two reactions (i.e., hydroxylation and dichlorination) were thermodynamically favorable. Illumina MiSeq sequencing analyses revealed that DCF improved the populations of complex organic degradation microbes such as Proteiniclasticum and Tissierellales, which was in accord with the chemical analyses above. This work updates the fundamental understanding of the degradation of DCF in WAS anaerobic fermentation process and enlightens engineers to apply theoretical calculation to the field of sludge treatment or other complex microbial ecosystems. Graphical abstract: Image 1 Highlights: Approximately 28.8% of DCF was degraded during anaerobic fermentation system. DCF reduced the diversity and complexity of microbial community. Hydroxylation and dichlorination reactions were thermodynamically favorable. Proteiniclasticum and Tissierellales may be microbes related to DCF degradation.